Diagnostic challenges in systemic amyloidosis: a case report with clinical and laboratorial pitfalls - Angelina Maria Martins Lino; Jussara Bianchi Castelli; Roberta Shcolnik Szor; Fabio Fernandes; Vera Demarchi Aiello (University of São Paulo, 2021)
Currently, there is growing evidence in the literature warning of misdiagnosis involving amyloidosis and chronic inflammatory demyelinating polyneuropathy (CIDP). Although inducing clinical manifestations outside the peripheral nervous system, light chain and transthyretin amyloidosis may initially present with peripheral neuropathy, which can be indistinguishable from CIDP, leading to a delay in the correct diagnosis. Besides, the precise identification of the amyloid subtype is often challenging. This case report exemplifies clinical and laboratory pitfalls in diagnosing amyloidosis and subtyping amyloid, exposing the patient to potentially harmful procedures